Aqueous phase reforming of polyols for hydrogen production using supported PtFe bimetallic catalysts. (September 2016) - Kim, Min-Cheol; Kim, Tae-Wan; Kim, Hyung Ju; Kim, Chul-Ung; Bae, Jong Wook
Abstract: 3-D cubic ordered mesoporous carbon (CMK-9) supported PtFe bimetallic catalysts with a range of PtFe compositions were applied to the aqueous phase reforming (APR) of polyols for hydrogen production. The catalytic performance with respect to the polyol and support used was also studied. The catalysts and supports were characterized via X-ray powder diffraction (XRD), transmission electron microscopy (TEM), N2 sorption, temperature programmed reduction (TPR), and CO chemisorption techniques. The polyols investigated include ethylene glycol (EG), glycerol, xylitol, and sorbitol. It was found that the addition of Fe to the Pt/CMK-9 catalyst significantly improved catalytic performance, with the optimum Pt:Fe ratio for APR activity being 1:3. It was also observed that, in the PtFe (1:3) system, the CMK-9 support demonstrated better catalytic performance than commercially available activated carbon or alumina. In addition, the catalytic activity of the PtFe/CMK-9 catalyst was successfully increased by both the effect of the water-gas shift reaction, promoted by Fe addition to Pt, and by the structural properties and nature of the CMK-9 support. Moreover, the PtFe (1:3)/CMK-9 catalyst showed efficient catalytic activity for different biomass derivatives (EG, glycerol, xylitol, and sorbitol), with the activity decreasing with increase in the number of carbon atoms. Graphical abstract: Highlights: Carried out aqueous phase reforming (APR) reactions of polyols. Prepared a 3-D hollow-type ordered mesoporous carbon supported PtFe catalyst. Studied the effect of different polyol feed and support. The addition of Fe to the Pt/CMK-9 catalyst improved catalytic APR performance. The optimum Pt:Fe ratio for APR reaction was 1:3.